PENGARUH KURIKULUM, LINGKUNGAN PENDIDIKAN, DAN SARANA PRASARANA BELAJAR TERHADAP PRESTASI BELAJAR SISWA DI SEKOLAH MENENGAH PERTAMA NEGERI 1 PAGU KABUPATEN KEDIRI - Anita Sumelvia Dewi (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2017)
The research aims to analyze the Factor Influencing Student Achievment Junior High School 1 Kediri. The hypothesis tested in this study were (1) there is significant effect partial curriculum on student achievement, (2) there was a significant effect of partial environmental education on student achievement, (3) there was significant effect of partial education infrastructure on student achievement, (4) there are simultans effect of curriculum, education environment, and insfrastructure on student achievement. The result of descriptive analysis it was revealed that student achievement SMPN 1 Pagu Kediri in both categories (56,5%), curriculum in both of the data analysis using Multiple Linear Regression Analysis show (1) the curriculum has a significant impact on student achievement t-hit >t-tab (4,692 > 1,656) with a significant level of 0,000 (2) education environment have significant impact on academic achievement students t-hit > t-tab (3,623 > 1,656) with asignificant level of 0,001 (3) education infrastructure has a significant impact on student achievement t-hit > t-tab (3,858 > 1,656) with a significant level of 0,001 (4) together curriculum, education environment, and education infrastructure has significant influence on student achievement F-hit >F-tab (5,558 > 3,276), with a significant level of 0,001 with the effective contribution of 77,5% (R square =0,775).